Drug Utilization Review of Potassium Chloride Injection Formulations Available in a Private Hospital in Kuching, Sarawak, Malaysia - Melissa, Mohammad Hirman; Azmi, Sarriff (Penerbit Universiti Sains Malaysia, 2013)
Background: The concentrated potassium chloride injection is a high-alert medication and replacing it with a pre-mixed formulation can reduce the risks associated with its use. The aim of this study was to determine the clinical characteristics of patients receiving different potassium chloride formulations available at a private institution. The study also assessed the effectiveness and safety of pre-mixed formulations in the correction of hypokalaemia.